Climate change adaptation options in rainfed upland cropping systems in the wet tropics: A case study of smallholder farms in North-West Cambodia. (1st November 2016) - Touch, Van; Martin, Robert John; Scott, Jeannette Fiona; Cowie, Annette; Liu, De Li
Abstract: While climate change is confirmed to have serious impacts on agricultural production in many regions worldwide, researchers have proposed various measures that farmers can apply to cope with and adapt to those changes. However, it is often the case that not every adaptation measure would be practical and adoptable in a specific region. Farmers may have their own ways of managing and adapting to climate change that need to be taken into account when considering interventions. This study aimed to engage with farmers to: (1) better understand small-holder knowledge, attitudes and practices in relation to perceived or expected climate change; and (2) document cropping practices, climate change perceptions, constraints to crop production, and coping and adaptation options with existing climate variability and expected climate change. This study was conducted in 2015 in Sala Krau village near Pailin (12°52′N, 102°45′E) and Samlout (12°39′N, 102°36′E) of North-West Cambodia. The methods used were a combination of focus group discussions and one-on-one interviews where 132 farming households were randomly selected. We found that farmers were conscious of changes in climate over recent years, and had a good understanding of likely future changes. While farmers are aware of some practices that can be modified to minimize risk and cope with anticipated changes, they are reluctant to apply them. Furthermore; there are no government agricultural extension services provided at the village level and farmers have relied on each other and other actors in the value chain network for information to support their decision-making. There is a lack of knowledge of the principles of conservation agriculture that urgently require agricultural extension services in the region to build farmer ability to better cope and adapt to climate change. Highlights: Effective climate change adaptation measures must consider farmer knowledge. A case study of 132 small-holder farmers in regional North-West Cambodia was used. Farmers were aware of adaptation practices to cope with anticipated climate changes. Incomplete knowledge and resources meant they were reluctant to apply the practices. The methodology used is also applicable to other developing countries.